Sosialisasi Dan Pendidikan Kesehatan Metode Mencuci Tangan Yang Baik Dan Benar Pada Ibu Hamil - Asmirah, Rika; Ningsih, Eka Sarofah; Delimayani, Delimayani; Sembiring, Endam Apulina br.; Anggeraeni, Anggeraeni; Mustamin, Rini (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Regulation of the Minister of Health concerning Community-Based Total Sanitation as stated in the Decree of the Minister of Health of the Republic of Indonesia No. 852/SK/Menkes/IX/2008 states that hand washing with soap is the behavior of washing hands using running water and soap. Pregnant women are at high risk of infection, this is due to the body's low immune system, so pregnant women are more susceptible to disease. One way to prevent transmission is to wash your hands regularly with soap and water or a hand sanitizer containing 60% alcohol. especially after activities outside the home or in public places. The aim of this Community Service Activity (PkM) is to increase the knowledge of pregnant women and improve their ability to wash their hands effectively. The method used is socialization and health education on proper and correct hand washing methods for pregnant women. The results of Community Service (PkM) activities went well and pregnant women were very enthusiastic about participating in Community Service (PkM) activities until completion and there were also changes in increasing mothers' knowledge and ability to wash their hands effectively as part of prevention efforts. The conclusion is that the Community Service Team (PkM) hopes that health workers will always pay attention and use it as a work program so that they can reduce morbidity and mortality rates.